2004
DOI: 10.1002/acp.1072
|View full text |Cite
|
Sign up to set email alerts
|

Is the cart pushing the horse? the effects of child characteristics on children's and adults' interview behaviours

Abstract: In the current study we examine the influence of child individual differences on children's and adults' behaviours in unstructured forensic interviews. Thirty-eight interviews conducted by actual forensic interviewers with 3-to 7-year-old children were analysed for child reporting behaviours (assent, denial, acquiescence, accurate and inaccurate details, verbosity and cooperation) and adult behaviours (leading vs. neutral questions). Consistent with our predictions, child individual differences that were visib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 44 publications
2
32
2
Order By: Relevance
“…The current study sought to replicate previous results conducted in other comparable studies (e.g., Gilstrap & Ceci, 2005;Gilstrap & Papierno, 2004) with a new sample.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…The current study sought to replicate previous results conducted in other comparable studies (e.g., Gilstrap & Ceci, 2005;Gilstrap & Papierno, 2004) with a new sample.…”
Section: Discussionmentioning
confidence: 50%
“…Some studies have found that children with higher IQ scores are less suggestible (Danielsdottir, Sigurgeirsdottir, Einarsdottir, & Haraldsson, 1993;McFarlane, Powell, & Dudgeon, 2002;Pollard et al, 2004, although see discussion of range issues; Young, Powell, & Dudgeon, 2003), produce more details during general recall (Roebers & Schneider, 2001), and behave more co-operatively in interviews (Gilstrap & Papierno, 2004). Others have found no relationship between intelligence and suggestibility (Bruck, Ceci, Francoeur, & Barr, 1995;Roebers & Schneider, 2001).…”
Section: Downloaded By [University Of Chicago Library] At 23:59 19 Dementioning
confidence: 95%
See 2 more Smart Citations
“…Indeed, Gilstrap and Papierno (2004) found that interviewers posed more leading questions to shy and withdrawn children than to socially competent ones. Following this line of argument, the child providing new relevant information might be expected to influence the interviewers' interviewing style in a positive way, decreasing the use of focused and, in particular, suggestive questions-particularly since interviewers are recommended to follow-up information by the children as much as possible by means of open-ended questions or encouragement to continue (e.g., Poole & Lamb, 1998;Wilson & Powell, 2001).…”
Section: Interviewing Techniques and Follow-up Questions In Child Sexmentioning
confidence: 97%